Research of the Dynamics of Varying-coefficient-shift-modification Gear based on ADAMS - Hou Yujie; Han Jiguang; Shao Minghui; Jiang Jiuliang; Chen Siyao (Jixie chuandong)
Taking the varying- coefficient- shift- modification gear transmission system as study object,the dynamic characteristics are studied. The dynamics simulation model of varying- coefficient- shift- modification gear transmission system is established based on the software of Matlab,Pro / E and ADAMS. The curves of changing contact force and vibration characteristic are obtained. The simulation results show that,the varying- coefficient- shift- modification gear has the characteristic transmission steady,contact force of gears and angular acceleration change regular. The vibration caused by the backlash of eccentric- involutes gears is effectively reduced,it has a strong application value in the practical engineering.